Financial Results of Government Units Sector of Ukraine - Kondratyuk, Irina (Finansowe wyniki sektora jednostek rządowych Ukrainy, 2010)
The application of cash method in budget execution accounting and accrued method in budgetary funds administrators (BFA) accounting is the cause of differences in separate operations in actual determination of the same accounting object. The financial results of BFA activity as government units, including social security funds sector institutions, and as primary units of budget system are performed rather as an indicator of budgetary funds efficiency than an indicator of financial results activity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 47-53
Keywords: cash method; budget; BFA